2012 IEEE 26th International Parallel and Distributed Processing Symposium Workshops &Amp; PhD Forum 2012
DOI: 10.1109/ipdpsw.2012.91
|View full text |Cite
|
Sign up to set email alerts
|

A Speculative HMMER Search Implementation on GPU

Abstract: Due to the exponentially growing bioinformatics databases and rapidly popular of GPU for general purpose computing, it is promising to employ GPU techniques to accelerate the sequence search process. Hmmsearch from HMMER bioinformatics software package is a wildly used software tool for sensitive profile HMM (Hidden Markov Model) searches of biological sequence databases. In this paper, we implement a speculative hmmsearch implementation on NVIDIA Fermi GPU and apply various optimizations to it. We test the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Moreover, in recent years in order to take advantages of new high performance hardwares, several works on accelerating HMMER on GPUs have been reported such as [61] in 2010 and [62] in 2012. And Oliver et al [63] reported their work on accelerating HMMER searching using FPGAs in 2008.…”
Section: Taxonomymentioning
confidence: 99%
“…Moreover, in recent years in order to take advantages of new high performance hardwares, several works on accelerating HMMER on GPUs have been reported such as [61] in 2010 and [62] in 2012. And Oliver et al [63] reported their work on accelerating HMMER searching using FPGAs in 2008.…”
Section: Taxonomymentioning
confidence: 99%
“…Previous research on GPU-based acceleration of algorithms related to HMMs (Hidden Markov models) in computational biology mainly focuses on HMMer, which is a software suite for protein sequence similarity calculation using probabilistic models called profile hidden Markov models (profile-HMMs) [8] [9]. However, the input of the profile-HMMs forward algorithm in HMMer is composed of a sequence and a reference database, which is much different from the input of PFA in the GATK HaplotypeCaller.…”
Section: B Related Workmentioning
confidence: 99%
“…The number of gene sequence alignment tasks reaches more than one million. Therefore, many researchers use parallel platforms [13] such as multi-core CPUs [9,14], GPUs [15,16,17,18,19] and Field Programmable Gate Arrays (FPGAs) [20,21,22,23,24,25] to develop parallelism in gene sequence alignment applications. Compared with CPUs and GPUs, FPGA chips serve as custom hardware for the computing-intensive applications with numerous computing and storage resources [26,27].…”
Section: Introductionmentioning
confidence: 99%